Dynamics of the gas-plasma torch formed by the highcurrent electron beam action on solid targets - Klepikov, V.F.; Lytvynenko, V.V.; Lonin, Yu.F.; Ponomarev, A.G.; Tolstolutskiy, O.G.; Uvarov, V.V.; Uvarov, V.T. (Вопросы атомной науки и техники, 2009)
The interaction of high-current REВ with the surface of solid targets was investigated. The target material was
stainless steel 12Х18Н10Т, graphite, tungsten, plexiglas. The optical diagnostic methods were used to determine the
space-time characteristics of a gas-plasma torch (GPT), formed as a result of the tubular microsecond REB action on the
surface of solid targets. The times of GPT formation and its spread velocity (transverse and longitudinal) for different
materials were determined. An axial focus of GPT, moving towards the beam, was found. Досліджувалась взаємодія сильнострумового РЕП з поверхнею твердотільних мішеней, в якості котрих були
нержавіюча сталь 12Х18Н10Т, графіт, вольфрам та органічне скло. За допомогою оптичних методів діагностики
отримано просторово-часові характеристики газоплазмового факела (ГПФ), який утворювався при дії
трубчастих РЕП мікросекундної тривалості на поверхню твердотільних мішеней. Отримано час утворення
газоплазмового факела, поперечна і повздовжня швидкість його розльоту для різних матеріалів. Виявлено
утворення осьового фокуса ГПФ, який рухається назустріч пучку Исследовалось взаимодействие сильноточного РЭП с поверхностью твердотельных мишеней, в качестве
которых служили нержавеющая сталь 12Х18Н10Т, графит, вольфрам, оргстекло. С помощью оптических
методов диагностики получены пространственно-временные характеристики газоплазменного факела (ГПФ),
образованного при воздействии трубчатых релятивистских электронных пучков микросекундной длительности
на поверхность твердотельных мишеней. Определены времена образования ГПФ, поперечная и продольная
скорости его разлета для различных материалов. Обнаружено образование осевого фокуса ГПФ, который
распространяется навстречу пучку.